The New international dictionary of New Testament theology Vol.2 - Brown, Colin, 1932-; Coenen, Lothar (Carlisle, Cumbria, UK The Paternoster Press, 1986)
Contains articles that explore the meaning and use of the key terms of the New Testament, each with discussion of the word in classical and secular Greek, in the Old Testament, and in the New Testament; arranged alphabetically in English, with associated Greek words and transliterations.
volume 1. A-F -- volume 2. G-Pre -- volume 3. Pri-Z -- volume 4. Indexes / general index compiled by Norman Hillyer ; Scripture index and index to extrabiblical literature compiled by David Townsley and Russell Bjork.
"Translated, with additions and revisions, from the German Theologisches Begriffslexikon zum Neuen Testament, edited by Lothar Coenen, Erich Beyreuther, and Hans Bietenhard."
"Companion volume: The new international dictionary of the Christian Church."
Originally published in 3 volumes (1975-1978) by Zondervan Publishing House. Reissued here in 4 volumes. Volume 4 contains the indexes to volumes 1-3.
Keywords: Bible. -- Theology -- Dictionaries; Bible. -- Dictionaries